Prospek Usaha Bagi Hasil Penanaman Jati Unggul Nusantara (Studi Kasus Pada Koperasi Perumahan Wanabhakti Nusantara di Kabupaten Bogor) - Muhammad Noor Efansyah; M Hasjim Bintoro; W H Limbong (Institut Pertanian Bogor, 2012)
Planting crops clones Jati Unggul Nusantara (JUN) in the area of Bogor Regency is a business model that was developed for the Koperasi Perumahan Wanabhakti Nusantara (UBH-KPWN), involving investors, landowners, community manager of the plant (farmers) and the village officials. The activity aims to distribute capital to the community, land use has not been productive, providing a source of teak wood supply for industry and as a provider of employment for the community. JUN investment in Cogreg Village, Parung District, Bogor regency, has been carried out since three years ago (starting in 2007). Offsetting JUN plants will be harvested in the fifth year (year 2012), promising to five parties, will receive revenue sharing from the sales value of timber harvest JUN. JUN three years old plant in Bogor regency, totaling 6.075 trees, potential measurements in a sampling plant 2.5% of the total population. The result of the potential crop average diameter of 0.11 m/tree and average branch free height 4.74 m/tree, calculate the average volume of 0.044 m3/tree or 44 m3/ha, bringing the total potential of the plant three years 266.28 m3. Appropriate considering the growth potential and risk of death of plants, the projected average volume increment 0.021 m3/year or 21 m3/ha/year. Harvest prospects in the fifth year calculated in the range 86 up to 100 m3/ha, or an average of 91 m3/ha. Base on projection teak wood basic sale prices (sortiment A1 tipe D quality P - M), in the fifth year from Rp2,135,000 up to Rp2,408,000. So the prospect of selling the timber JUN between Rp988.630.584 up to Rp1.462.925.329, or an average selling of Rp1.279.294.179. Based on the prospect for timber harvest and JUN timber sale values, then the appropriate financial analysis (NPV, IRR, and B/C) is very reasonable business activities are managed. Calculated value for the outcome of each the party, according to the average revenue outlook; (1) Investors Rp591.376.022, (2) Land Owners Rp147.844.005, (3) Farmers Rp270.-037.076, (4) UBH KPWN Rp162.022.246, (5) Village Officials Rp108.014.830.